PRO DAN KONTRA PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY DAN PERENCANAAN PAJAK TERHADAP MANAJEMEN LABA PADA SUB-SEKTOR INDUSTRI MANUFAKTUR: PERSPEKTIF STAKEHOLDER THEORY - Dewi, Putu Purnama; Sugiantari Putri, Ni Putu Pradnya (Jurnal Akuntansi dan Pajak, 2024)
This study explores the pros and cons of Corporate Social Responsibility (CSR) disclosure and tax planning on earnings management in the manufacture industry using a literature review method and stakeholder theory perspective. CSR and tax planning are two practices commonly employed by companies to enhance their image and financial efficiency. CSR disclosure can enhance reputation and investor trust but also incurs high costs and greenwashing risks. Effective tax planning can reduce tax burdens but carries legal and reputational risks. Through stakeholder theory, this study emphasizes the importance of considering the interests of various stakeholders in earnings management decisions. The results provide insights into balanced and sustainable strategies for companies in the manufacture industry, considering the long-term impacts of CSR and tax planning.